One-step phosphorization synthesis of CoP@NiCoP nanowire/nanosheet composites hybrid arrays on Ni foam for high-performance supercapacitors - Wang, Xin; Jing, Chuan; Zhang, Wenzheng; Wang, Xiushuang; Liu, Xiaoying; Dong, Biqin; Zhang, Yuxin (Applied surface science, 2020)
[Display omitted] •Facial synthesis of core–shell like structure on Ni foam.•A compound of two phosphides prepared by one-step phosphorization process.•Enhanced electrochemical performance by phosphorization. The transition metal phosphides have been gradually used in supercapacitors due to its excellent conductivity and electrochemical activity. In this work, the novel composite CoP@NiCoP directly grown on Ni foam was prepared by a facial two-steps hydrothermal and one-step phosphorization method. The CoP nanowires serve as the skeleton and conductive pathway for NiCoP nanosheets and the active material involved in electrochemical process to provide extra capacitance. With the skeleton of CoP nanowires, NiCoP nanosheets have more sites to anchor and can transfer electrons quickly. Taking advantage of structure and transition phosphides, the CoP@NiCoP possesses a superior specific capacitance of 1911.6 F g−1 (265.5 mAh g−1) at 2 A g−1, outstanding rate performance with 61.68% retention even at 25 A g−1 and good cycling stability with 73.3% capacitance retention after 1000 cycles at 25 A g−1. In addition, an asymmetric supercapacitor (ASC) consisted by CoP@NiCoP and the Fe2O3 derived from Fe-based MOF delivers a satisfactory energy density of 37.16 Wh kg−1 at the corresponding power density of 875 W kg−1. The excellent electrochemical performance verifies the effectiveness of the composite structure and transition phosphides and thus provide a novel strategy for the further design of high performance supercapacitors.